Alternative Substrate Metabolism in Yarrowia lipolytica - Spagnuolo, Michael; Shabbir Hussain, Murtaza; Gambill, Lauren; Blenner, Mark (Frontiers in Microbiology, 2018)
Recent advances in genetic engineering capabilities have enabled the development of oleochemical producing strains of Yarrowia lipolytica. Much of the metabolic engineering effort has focused on pathway engineering of the product using glucose as the feedstock; however, alternative substrates, including various other hexose and pentose sugars, glycerol, lipids, acetate, and less-refined carbon feedstocks, have not received the same attention. In this review, we discuss recent work leading to better utilization of alternative substrates. This review aims to provide a comprehensive understanding of the current state of knowledge for alternative substrate utilization, suggest potential pathways identified through homology in the absence of prior characterization, discuss recent work that either identifies, endogenous or cryptic metabolism, and describe metabolic engineering to improve alternative substrate utilization. Finally, we describe the critical questions and challenges that remain for engineering Y. lipolytica for better alternative substrate utilization.